Experimental analysis of gyroscopic effect on vehicle vibration and accident potential - Noor Hazira, Mohamad Haidzir (2010)
This thesis concerns with the experimental analysis of gyroscopic effect on vehicle vibration and accident potential. The objective of this thesis is to investigate the vehicle vibration, roll and yaw limits in various driving maneuver. The thesis describes the method to collect the vehicle’s centre of gravity performance in term of moment and movement. The centre of gravity is assumed as the vehicle rigid body. Uncontrolled roll and yaw moment will cause different impact as it reach the limit depends on the contributed factors and condition. Due to variation of design, different geometry and external influences, study on roll and yaw will be different for every type of car. Thus, it is important to study and to address the relationship of centre of gravity performance and moment limit to reduce accident tendency due to uncontrolled roll and yaw moment. Three different driving maneuver had been evaluate for this study purpose which are steady state cornering with constant radius, load and lane change maneuver. The test is perform in Universiti Malaysia Pahang (UMP) and the data used for the analysis is obtained test using UMP Test Car which has been installed with MTi (gyroscope), Global Positioning System and DEWESoft software for data acquisition purpose. The post-processing method was performed using Flexpro and Microsoft Office Excel. The post-processing method to determine the roll and yaw angle is being done in Flexpro using the FPScript function. Finally, the results of analysis were represented in graph. From the graphs represented, some discussions are made according to the experiment performed. Comparisons of all the tests are made in achieving the conclusion. It is observed that the roll and yaw have its own limits based on the CG performance of the vehicle. The results concluded that the limit is strongly dependent to the turning radius and load variation. For steady state cornering, R3 is the limit for roll while R4 is the limit for yaw. As for the load variation, 50 kg load give the most uncontrolled roll and yaw. At 30 km/h for lane change test, the yaw is uncontrollable and roll is uncontrolled at 60 km/h. Improvements can be made by finding the exact location of CG that will give the exact limits of a vehicle. Finally, the methods and results for verification in this thesis are only applicable for passenger car.